The C-terminal segment of yeast BMH proteins exhibits different structure compared to other 14-3-3 protein isoforms - Veisová, Dana; Řežábková, Lenka; Štěpánek, Miroslav; Novotná, Pavlína; Heřman, Petr; Večeř, Jaroslav; Obšil, Tomáš; Obšilová, Veronika (Biochemistry (Easton), 2010)
Yeast 14-3-3 protein isoforms BMH1 and BMH2 possess a distinctly variant C-terminal tail which differentiates them from the isoforms of higher eukaryotes. Their C-termini are longer and contain a polyglutamine stretch of unknown function. It is now well established that the C-terminal segment of 14-3-3 proteins plays an important regulatory role by functioning as an autoinhibitor which occupies the ligand binding groove and blocks the binding of inappropriate ligands. Whether the same holds true or not for the yeast isoforms is unclear. Therefore, we investigated the conformational behavior of the C-terminal segment of BMH proteins using various biophysical techniques. Dynamic light scattering, sedimentation velocity, time-resolved fluorescence anisotropy decay, and size exclusion chromatography measurements showed that the molecules of BMH proteins are significantly larger compared to the human 14-3-3zeta isoform. On the other hand, the sedimentation analysis confirmed that BMH proteins form dimers. Time-resolved tryptophan fluorescence experiments revealed no dramatic structural changes of the C-terminal segment upon the ligand binding. Taken together, the C-terminal segment of BMH proteins adopts a widely opened and extended conformation that makes difficult its folding into the ligand binding groove, thus increasing the apparent molecular size. It seems, therefore, that the C-terminal segment of BMH proteins does not function as an autoinhibitor.
Keywords: terciární struktura proteinů; proteiny 14-3-3; Amino Acid Motifs; Protein Conformation; Saccharomyces cerevisiae Proteins; sekvenční seřazení; dimerizace; Molecular Sequence Data; Amino Acid Sequence; Humans; Sequence Alignment; Dimerization; sekvence aminokyselin; Saccharomyces cerevisiae; Saccharomyces cerevisiae - proteiny; lidé; 14-3-3 Proteins; Protein Structure, Tertiary; konformace proteinů; molekulární sekvence - údaje; aminokyselinové motivy